The evaluation of green infrastructure elements to enhance green neighbourhood park in Shah Alam, Selangor / Rijal Saffuan, Khalid Zanudin and Puziah Ahmad - Saffuan, Rijal; Zanudin, Khalid; Ahmad, Puziah (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
Green infrastructure is an effort of countering the negative impact caused by the climate change and urban sprawl This green infrastructure basically consists of diverse green spaces which are interconnected and linked by the streets, waterways and drainage network in urban areas. The purpose of the study is to apply the implementation of green infrastructure concept as a medium to enhance the neighbourhood park using green infrastructure concept and principle in Section 6, Section 7, and Section 8, Shah Alam. The analysis has been done to determine the current provision of green infrastructure elements within the study area based on the concept of green infrastructure. Green infrastructure consists of several components that work and function together to maintain the green network of physical environment. The components refer to the combination of hub and links where hub is the neighbourhood park and link is the landscape and pedestrian walkways. The level of green infrastructure is assessed through site inventory on aspects of provision, maintenance, accessibility, and image/character. The outcomes of the analysis are used to evaluate the efficiency of current provision of green infrastructure in enhancing the neighbourhood park in the study area before proposing an improvement provision of green infrastructure within the study area. The findings could be used by local authority to formulate plan and guidelines in developing infrastructure and facilities that fulfill green infrastructure elements to enhance the neighbourhood park.